2014
DOI: 10.1371/journal.pone.0097797
|View full text |Cite
|
Sign up to set email alerts
|

Serum Stability and Physicochemical Characterization of a Novel Amphipathic Peptide C6M1 for SiRNA Delivery

Abstract: The efficient delivery of nucleic acids as therapeutic agents is a major challenge in gene therapy. Peptides have recently emerged as a novel carrier for delivery of drugs and genes. C6M1 is a designed amphipathic peptide with the ability to form stable complexes with short interfering RNA (siRNA). The peptide showed a combination of random coil and helical structure in water but mainly adopted a helical conformation in the presence of anions or siRNA. Revealed by dynamic light scattering (DLS) and microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 31 publications
5
27
0
Order By: Relevance
“…This determined also the behavior of these polyplexes in the gel retardation assay. These data are in agreement with those obtained in other similar studies with polycations (Jafari et al, 2014). Based on these results, we chose to carry on the following experiments with two ratios, one corresponding to a condition of partially complexation (w/w of 0.5 = R1) and another corresponding to a full complexation (w/w of 5 = R2).…”
Section: Resultssupporting
confidence: 85%
“…This determined also the behavior of these polyplexes in the gel retardation assay. These data are in agreement with those obtained in other similar studies with polycations (Jafari et al, 2014). Based on these results, we chose to carry on the following experiments with two ratios, one corresponding to a condition of partially complexation (w/w of 0.5 = R1) and another corresponding to a full complexation (w/w of 5 = R2).…”
Section: Resultssupporting
confidence: 85%
“…Hence, all micelle/pDNA complexes were prepared in HEPES buffer due to the low ionic strength of buffer for further experiments. Also our results compatible with the Jafari et al [25] indicated that the media were considerably important on the particle size and charge. Moreover, these results indicated that both PPP30 and PPP60 micelle/DNA complexes had desirable size for biological applications and could be passively targeted by EPR effect [26,27].…”
Section: Micelle Formulations (Blank)supporting
confidence: 93%
“…The results exhibited that both PPP30 and PPP60 micelle/DNA complexes had excess positive charge at highest N/P ratio (Figure 3(B,F)). These results supported the observations of particle size that excess cationic charge leading to small particle size due to high repulsion of particles causes to prevent the aggregation [9,25]. Hence, all micelle/pDNA complexes were prepared in HEPES buffer due to the low ionic strength of buffer for further experiments.…”
Section: Micelle Formulations (Blank)supporting
confidence: 83%
“…Similar approaches were used for other non-covalent CPPs such as Pep-3 for HypNA-pPNA [49], CADY, C6 and MPEG-PCL-CH2R4H2C for siRNA condensation [126][127][128][129]. Fluorescence assays were also combined to circular dichroism (CD) analyses to monitor conformational changes that might occur in the presence of the ON and during CPP:ON complex formation [125,[128][129][130]. Although both fluorescence and CD investigations suggest interactions and formation of CPP:ON complexes, the use of gel shift assays has been generalized to demonstrate the formation of complexes [124,131].…”
Section: Formulation Of Peptide-based Nanoparticles (Pbns)mentioning
confidence: 99%
“…For other CPP:ON complexes, the size and the biological activity clearly vary with the MR [50]. Size and charge can also depend on the environment which is important since nanoparticles stability and homogeneity might vary according to the nature of the buffer, as described for C6M1:siRNA particles [130]. In addition physiological conditions such as serum addition can influence colloidal properties.…”
Section: Formulation Of Peptide-based Nanoparticles (Pbns)mentioning
confidence: 99%